Effects of visual and aural communication of categorical response options on answers to survey questions - Peter Lynn; Steven Hope; Annette Jäckle; Pamela Campanelli; Gerry Nicolaas (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Whether questions and answers are transmitted between interviewer and respondent by visual or aural communication can affect the responses given. We hypothesise that communication channel can affect either the respondent's understanding of the question or the tendency to satisfice. These effects may be mediated by the cognitive ability and motivation of the respondent and by the type and difficulty of the question. We test our hypotheses using data from a large-scale controlled experiment. We find support for the notion that visual presentation improves understanding of the question and reduces the tendency to satisfice. We also find that effects are stronger for respondents of higher cognitive ability and for motivated respondents.
Keywords: C81; C83; 330; cognitive ability; end-labelled scales; primacy effect; recency effect; respondent motivation; response order; satisficing